2013
DOI: 10.1051/eas/1364045
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismology of binary stars and a compilation of core overshoot and rotational frequency values of OB stars

Abstract: Abstract. After a brief introduction into the asteroseismic modelling of stars, we provide a compilation of the current seismic estimates of the core overshooting parameter and of the rotational frequency of single and binary massive stars. These important stellar parameters have meanwhile become available for eleven OB-type stars, among which three spectroscopic pulsating binaries and one magnetic pulsator. We highlight the potential of ongoing and future analyses of eclipsing binary pulsators as essential la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
14
1
Order By: Relevance
“…And the other way around, the "Group2" stars would then be intrinsically rapid rotators whose outer layers got spun down due to the angular momentum extracted from them by the IGWs. However, this hypothesis still contradicts the asteroseismic findings by [2] who found no correlation between the surface nitrogen abundance and the rotational frequency/projected rotational velocity of the star based on the multivariate statistical analysis of a sample of 70 B-type stars. Nevertheless, the IGWs can still be (and probably are) largely involved in the transport of the chemical elements inside stars.…”
Section: Internal Gravity Wavescontrasting
confidence: 61%
See 2 more Smart Citations
“…And the other way around, the "Group2" stars would then be intrinsically rapid rotators whose outer layers got spun down due to the angular momentum extracted from them by the IGWs. However, this hypothesis still contradicts the asteroseismic findings by [2] who found no correlation between the surface nitrogen abundance and the rotational frequency/projected rotational velocity of the star based on the multivariate statistical analysis of a sample of 70 B-type stars. Nevertheless, the IGWs can still be (and probably are) largely involved in the transport of the chemical elements inside stars.…”
Section: Internal Gravity Wavescontrasting
confidence: 61%
“…As it has been shown by [2], an extra mixing needs to be introduced in the terms of the core overshoot into the evolutionary models to match them with the observed seismic properties of binary components. However, it is barely the case for the majority of single stars of similar mass, where about the standard value of the core overshoot α = 0.2 is preferred, probably because the mass of a star can be way more relaxed in the modelling compared to the case of binary systems.…”
Section: Mass Discrepancymentioning
confidence: 99%
See 1 more Smart Citation
“…The DLEB samples in these investigations have typically been small, not exceeding a dozen or so systems (often far fewer), and have generally been restricted to the main sequence. Asteroseismic studies of single stars have so far been performed over limited ranges in mass and evolutionary state, but do suggest changes in overshooting that are not inconsistent with results described below (see, e.g., Aerts 2013;Deheuvels et al 2016).…”
Section: Introductionmentioning
confidence: 61%
“…These authors reported hints that α ov may depend on mass even over this narrow range. Similar seismic studies of more massive stars (M > 7 M ; Aerts 2013Aerts , 2015 reported no obvious mass dependence.…”
Section: Introductionmentioning
confidence: 63%